2017
DOI: 10.1038/bjc.2017.109
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study of temozolomide in pretreated metastatic colorectal cancer with MGMT promoter methylation

Abstract: Background:Presently, few options are available for refractory colorectal cancer (CRC). O6-methyl-guanine-DNA-methyltransferase (MGMT) promoter methylation is a frequent and early event in CRC tumourigenesis. This epigenetic silencing is a predictor of response to the alkylating drug temozolomide in glioblastoma. Preclinical evidences and some case reports showed temozolomide activity in CRC with MGMT silencing, but the available data from clinical trials are inconsistent.Methods:This was a multicentre, phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…2016 [ 56 ] Phase II, SA/second line in 11% of pts, third line or later in rest 37 CET + S-1 Previous IR, OX and FP, with PD on 5-FU Median PFS: 5.5 mos; 90% CI 4.4–5.7 ORR: 29.7%; 95% CI 15.9–47.0 DCR: 73.0%; CR n =1; PR: n =10; SD: n =16 Median OS: 13.5 mos; 95% CI 8.5–16.5 Median TTF: 4.6 mos; 95% CI 3.2–5.6 Rash: 27.0% Dry skin: 13.5% Anorexia: 10.8% Paronychia: 10.8% Fatigue: 10.8% Diarrhoea: 10.8% Mucositis: 10.8% Neutropaenia: 10.8% Leukopaenia: 2.7% Thrombocytopaenia: 2.7% Anaemia: 5.4% Elevated bilirubin: 8.1% Yoshida et al. 2016 [ 57 ] Phase II, SA/third line and later 31 BE + S-1 >2 previous regimens, including OX and IR DCR: 67.9%; 95% CI 47.6–84.1 CR: 0% PR: 0% SD: 67.9% Median TTF: 3.0 mos; 95% CI 1.8–4.3 Median PFS: 3.7 mos; 95% CI 2.1–5.6 Median OS: 8.6 mos; 95% CI 7.0–11.2 Anorexia: 20% Diarrhoea: 10% Nausea: 7% Fatigue: 7% Mucositis/stomatitis: 3% Rash/desquamation: 3% Decreased Hb: 17% Decreased bilirubin: 7% Neutropaenia: 3% Elevated ALT: 3% Elevated AST: 3% Calegari et al. 2017 [ 58 ] Phase II, SA/third line and later 41 TEM 2 previous, including FP, IR, OX, BE (and anti-EGFR for wt KRAS) ORR: 10% CR: 0% PR: 10% SD: 22% DCR: 32% Median PFS: 1.9 mos (range 1.6–2.35) Median OS: 5.1 mos...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2016 [ 56 ] Phase II, SA/second line in 11% of pts, third line or later in rest 37 CET + S-1 Previous IR, OX and FP, with PD on 5-FU Median PFS: 5.5 mos; 90% CI 4.4–5.7 ORR: 29.7%; 95% CI 15.9–47.0 DCR: 73.0%; CR n =1; PR: n =10; SD: n =16 Median OS: 13.5 mos; 95% CI 8.5–16.5 Median TTF: 4.6 mos; 95% CI 3.2–5.6 Rash: 27.0% Dry skin: 13.5% Anorexia: 10.8% Paronychia: 10.8% Fatigue: 10.8% Diarrhoea: 10.8% Mucositis: 10.8% Neutropaenia: 10.8% Leukopaenia: 2.7% Thrombocytopaenia: 2.7% Anaemia: 5.4% Elevated bilirubin: 8.1% Yoshida et al. 2016 [ 57 ] Phase II, SA/third line and later 31 BE + S-1 >2 previous regimens, including OX and IR DCR: 67.9%; 95% CI 47.6–84.1 CR: 0% PR: 0% SD: 67.9% Median TTF: 3.0 mos; 95% CI 1.8–4.3 Median PFS: 3.7 mos; 95% CI 2.1–5.6 Median OS: 8.6 mos; 95% CI 7.0–11.2 Anorexia: 20% Diarrhoea: 10% Nausea: 7% Fatigue: 7% Mucositis/stomatitis: 3% Rash/desquamation: 3% Decreased Hb: 17% Decreased bilirubin: 7% Neutropaenia: 3% Elevated ALT: 3% Elevated AST: 3% Calegari et al. 2017 [ 58 ] Phase II, SA/third line and later 41 TEM 2 previous, including FP, IR, OX, BE (and anti-EGFR for wt KRAS) ORR: 10% CR: 0% PR: 10% SD: 22% DCR: 32% Median PFS: 1.9 mos (range 1.6–2.35) Median OS: 5.1 mos...…”
Section: Resultsmentioning
confidence: 99%
“…A number of phase II, single-arm trials evaluated different investigational compounds in unselected patients receiving treatment beyond the second line, but did not indicate any clear survival benefit [ 49 , 50 , 52 , 53 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the initial trial with dacarbazine, responses according to RECIST criteria were observed only in 2 out of 68 patients, although all responders had tumors bearing MGMT promoter methylation [6]. Therefore, even if the trial failed to meet its primary endpoint of overall response rate (ORR), the biological rationale linking MGMT silencing with clinical benefit was considered strong enough to perform the subsequent temozolomide monotherapy trials in patients with mCRC who were molecularly selected for the presence of MGMT methylation [7][8][9][10][11]. In all these trials, methylation-specific PCR (MSP) was adopted as the assay for qualitatively detecting the presence or absence of T MGMT methylation, as previously validated for patients with glioblastoma [12].…”
Section: Mgmt Promoter Methylation As Predictive Biomarker Of Treatmementioning
confidence: 99%
“…Although phase II trials showed that TMZ is an active option in some pretreated patients with mCRC, it is not yet recognized as a standard option in current guidelines due to the lack of a formal comparison, the use of different drug schedules and heterogeneous techniques of detection of MGMT methylation and cut-off levels to define hypermethylation [98][99][100][101][102][103].…”
Section: Temozolomide + Immune Checkpoint Inhibitorsmentioning
confidence: 99%